Monstrous politics : geography, rights, and the urban revolution in Mexico City - Gerlofs, Ben A., 1985- (Critical Mexican studies., 2023)
"Tracing the evolving relationship between popular politics and the production of space through a fusion of historical geography and ethnography in Mexico City"--